Local fractal Fourier transform and applications - Golmankhaneh, Alireza Khalili; Ali, Karmina Kamal; Yilmazer, Resat; Kaabar, Mohammed Khalid Awad (Univ Tabriz, 2022)
In this manuscript, we review fractal calculus and the analogues of both local Fourier transform with its related properties and Fourier convolution theorem are proposed with proofs in fractal calculus. The fractal Dirac delta with its derivative and the fractal Fourier transform of the Dirac delta is also defined. In addition, some important applications of the local fractal Fourier transform are presented in this paper such as the fractal electric current in a simple circuit, the fractal second order ordinary differential equation, and the fractal Bernoulli-Euler beam equation. All discussed applications are closely related to the fact that, in fractal calculus, a useful local fractal derivative is a generalized local derivative in the standard calculus sense. In addition, a comparative analysis is also carried out to explain the benefits of this fractal calculus parameter on the basis of the additional alpha parameter, which is the dimension of the fractal set, such that when alpha = 1, we obtain the same results in the standard calculus.
Keywords: Fractal calculus; Fractal local Fourier transform; Fractal differential equation; Fractal Fourier convolution theorem; Fractal Dirac delta function